INTERAKSI PENDIDIKAN ISLAM - Akramun Nisa (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
As social humans beings will always be accompanied by a process of interaction or communication, interaction with the natural environment, interaction with others, as well as interaction with theLord, be it intentional or unintentional. There are various forms of interaction; especially regarding the interaction of a deliberate, there is an educational interaction term, which means the interactions take place to achieve the goals of education and teaching. These interactions include interactions in the process of learning and interaction in learning strategies. Interaction in the learning process in Islam always pay attention in respect the dignity, the dignity and freedom of thought, thus encouraging the learner's personality develop optimally, while for teachers, teaching is an obligation that has valuable service. It so happens for learning strategies in the context of education include;set of specifications and qualification and behavioral changes associated with the choice of approaches, procedures, methods and techniques of learning.